Hearts aglow eaudiobook Striking a match series, book 2. - Peterson, Tracie (Striking a Match, 2015)
A Romantic Times Lifetime Achievement Award recipient, CBA best-selling author Tracie Peterson is acclaimed for her blend of romance and adventure. In Hearts Aglow, Deborah Vandermark is pursuing her interest in medicine beside her beau Dr. Christopher Clayton. Although her West Texas lumber town isn't quite ready for a female physician, she has reason for hope. But she's blindsided when Christopher ends their relationship to return home to his troubled family.